A process to describe radiation damage at the molecular level. Application to the 125I seeds in water. (October 2018) - Colmenares, R.; Krupa, K.; Muñoz, A.; Blanco, F.; Williart, A.; García, G.
Abstract: The correlation between the absorbed energy and the induced biological damage still has unclear aspects, especially in the low energy and low dose rate irradiation regimes. From the knowledge of the molecular-induced effects (dissociations), it would be possible to better understand the side effects of radiation, such as induced cancers or damage to healthy tissue. With this in view, this paper presents results of a simulation of a 125 I-seed treatment with an event-by-event MC code (LEPTS) specifically designed to account for the low energy secondary particle interactions, such as electron attachment, vibro-rotational and neutral dissociation interactions. This calculation allowed us to analyze the potential radiation damage not only in connection with the energy deposition, but also in terms of induced molecular dissociations by taking into account ionizing and non-ionizing dissociative processes. We propose that this description of the molecular level damage be the basis for nanodosimetric evaluations. Highlights: Dose and the induced molecular dissociations evaluated as indicators of damage. This is done for 125 I in water by accounting for all the proven bond-breaking events. Important contributions to potential molecular damage via low energy collisions. For 125 I in water, the induced molecular damage is proportional to the absorbed dose. A procedure is established to evaluate molecular damage in other treatments.